Students Numeracy Skills on Social Arithmetic Problems in Context of Opi Tourism - Jariyah, Ainun; Zulkardi, Zulkardi; Susanti, Ely (Al-Khawarizmi, 2023)
This research uses descriptive technique and aims to determine student numeracy skills on Social Arithmetic Problems in Context of OPI Tourism. The subjects have been taken from class VI students in Palembang, totaling 3 people from odd semester students in the 2022/2023 academic year. While the data collection techniques used by researchers are interview tests and written tests. The indicator that often appears is using various numbers and symbols related to basic mathematics to solve problems in various contexts of everyday life and interpreting the results of the analysis to predict and make decisions Then, the indicator that rarely appears is analyzing the information displayed in various form (graphs, tables, charts, diagrams, etc)